Eksplorasi Self Efficacy Peserta Didik SMA pada Materi Sistem Peredaran Darah: Studi Deskriptif Terbatas - Ita Yuliastuti; Aripin Aripin; Liah Badriah; Diana Hernawati (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to explore the initial profile of high school students’ self-efficacy in Biology learning, particularly on the topic of the human circulatory system. A descriptive quantitative approach was employed, involving 36 eleventh-grade students from a public senior high school in Tasikmalaya City selected through purposive sampling. The research instrument consisted of a self efficacy questionnaire that had been validated by experts and developed based on Bandura’s theory, encompassing three main dimensions: level, magnitude, and strength. The instrument comprised 45 items measured using a 0–100 scale. The findings revealed that students’ self efficacy was categorized as moderate, with an overall percentage of 74%. Specifically, the magnitude and strength dimensions each reached 74%, while the generality dimension attained 76%. These results indicate that students possess a relatively adequate level of self confidence; however, it has not yet been fully optimized in dealing with complex learning tasks. Lower levels of self efficacy were also reflected in limited confidence, a high dependence on teachers, and low active participation in the learning process. Therefore, instructional innovations are needed to enhance students’ active engagement, such as the integration of computational thinking approaches and the use of virtual laboratories. This study provides important implications for the development of instructional strategies that not only emphasize cognitive achievement but also strengthen students’ affective aspects